Physico-mechanical characterization of a composite from sugar cane straw particles and alternative cements (2013)
Nowadays, sugar cane bagasse has applications as an alternative fuel in most of the sugar cane industries. However, other residues like sugar cane straw particles (SCSP), produced by mechanized harvesting, may be interesting for several applications, as a fuel or as a non-conventional aggregate for cement composite production, in this case partially replacing mineral aggregates. In this research, the behavior of a composite utilizing SCSP (replacing 33% of the sand, by volume) combined with four types of inorganic matrices was evaluated, one of them based on ordinary Portland cement (OPC) and three alternative matrices containing pozzolans by OPC replacement, such as ground fly ashes (GFA) and spent fluid catalytic catalyst for petrol (FCC) (A:100%OPC; B:50%OPC+50%GFA); C:50%OPC+40%GFA+10%FCC and D:50%OPC+30%GFA+20%FCC). Composite performance was evaluated daily by non-destructive ultrasonic test (NDT) and, after 28 days, by flexure and compression tests. Results showed the influence of the composite age on ultrasonic pulse velocity (UPV), finding a stabilization on UPV values at 28 days; and also the great influence of the matrix type on composite mechanical performance. Flexural and compressive strengths of composites with matrix A showed superiority when compared to the alternative matrices. Among them, matrix D showed superiority. In a general way, 33% (by volume) sand replacement by SCSP sharply decreased the composite´s mechanical performance: bending strength (a reduction of 9% to 24%) and compressive strength (a reduction of 38% to 53%). For matrices containing pozzolans, the decrease in mechanical performance was significantly lower.